A path to build basic Quantum Mechanics ideas in the context of light polarization and learning outcomes of secondary students. Issue 1 (May 2021) - Michelini, Marisa; Stefanel, Alberto
Abstract: There is consensus on the goal to introduce Quantum Mechanics in secondary school curricula for its paradigmatic role in the modern physics. In literature a wide spectra of proposals were developed and tested. With the goal to approach the basic ideas of quantum theory by means of active learning, we design a research based educational path in the context of light polarization, offering an open software environment for ideal experiments. Several Intervention Modules with secondary school students were performed, monitoring the learning paths by means of tutorials and pre-post-test for total about 900 students. Here a homogenous sample of 126 students is considered. Qualitative/quantitative data analysis shows coherent line of reasoning developed by students along the quantum concepts, coherent in some case with a hidden variables approach.